Freshwater Cyanotoxin Cylindrospermopsin Has Detrimental Stage-specific Effects on Hepatic Differentiation From Human Embryonic Stem Cells - Vanova, Tereza; Raska, Jan; Babica, Pavel; Sovadinova, Iva; Kunova Bosakova, Michaela; Dvorak, Petr; Blaha, Ludek; Rotrekl, Vladimir (Toxicological sciences, 2019)
Cylindrospermopsin (CYN) has been recognized as a potent waterborne hepatotoxin with an increasing environmental occurrence. However, CYN effects on the specific populations of hepatic cells involved in liver tissue development, renewal, and regeneration, have not been characterized yet. We used human embryonic stem cells to analyze the hepatic differentiation stage-specific effect of CYN. Our results strongly suggest that CYN might contribute to the development of chronic adverse outcomes by disrupting liver tissue homeostasis in terms of (1) cellular stress and damage induced in the mature differentiated hepatocytes, which was associated with a necrotic cell death and thus possibly also inflammatory responses; (2) selective elimination of HNF4α+ cells from populations of progenitor cells and immature hepatocytes during hepatic differentiation, which could possibly lead to an impaired liver renewal and regeneration; (3) impaired hepatic functions of immature hepatocytes, such as decreased albumin secretion or increased lipid accumulation, which could contribute to the development of liver steatosis; and (4) survival of the immature and AFP-expressing cells with the limited ability to further differentiate, which could represent a tumor-promoting condition.
Keywords: buněčná diferenciace; Cell Survival; játra; Oxidative Stress; metabolismus lipidů; oxidační stres; Humans; Lipid Metabolism; nekróza; Albumins; viabilita buněk; albuminy; lidé; uracil; lidské embryonální kmenové buňky; hepatocytární jaderný faktor 4; apoptóza; sladká voda; sinice; Stem Cells; Liver; Fresh Water; Hepatocyte Nuclear Factor 4; Bacterial Toxins; Cell Differentiation; Uracil; Human Embryonic Stem Cells; Hepatocytes; kmenové buňky; bakteriální toxiny; Cyanobacteria; hepatocyty; Necrosis; Apoptosis